An update on host immunity correlates and prospects of re-infection in COVID-19. (13th July 2022) - Negi, Neema; Maurya, Shesh Prakash; Singh, Ravinder; Das, Bimal Kumar
Abstract: Reinfection with SARS-CoV-2 is not frequent yet the incidence rate of it is increasing globally owing to the slow emergence of drift variants that pose a perpetual threat to vaccination strategies and have a greater propensity for disease reoccurrence. Long-term protection against SARS-CoV-2 reinfection relies on the induction of the innate as well as the adaptive immune response endowed with immune memory. However, a multitude of factors including the selection pressure, the waning immunity against SARS-CoV-2 over the first year after infection possibly favors evolution of more infectious immune escape variants, amplifying the risk of reinfection. Additionally, the correlates of immune protection, the novel SARS-CoV-2 variants of concern (VOC), the durability of the adaptive and mucosal immunity remain major challenges for the development of therapeutic and prophylactic interventions. Interestingly, a recent body of evidence indicated that the gastrointestinal (GI) tract is another important target organ for SARS-CoV-2 besides the respiratory system, potentially increasing the likelihood of reinfection by impacting the microbiome and the immune response via the gut-lung axis. In this review, we summarized the latest development in SARS-CoV-2 reinfection, and explored the untapped potential of trained immunity. We also highlighted the immune memory kinetics of the humoral and cell-mediated immune response, genetic drift of the emerging viral variants, and discussed the current challenges in vaccine development. Understanding the dynamics and the quality of immune response by unlocking the power of the innate, humoral and cell-mediated immunity during SARS-CoV-2 reinfection would open newer avenues for drug discovery and vaccine designs. Graphical Abstract: UF0001